2017
DOI: 10.17979/ejpod.2017.3.1.1711
|View full text |Cite
|
Sign up to set email alerts
|

Normas para referenciar la bibliografía consultada en los trabajos de investigación

Abstract: Research papers refer to documents, books, articles or other published information resources, which form the lists of references accompanying these works. So when a document cited is not only necessary that it is easily identifiable and accessible through bibliographic data reviewed, but also all references must be consistent with each other using a common model of consistency. The number of citation styles ranging from the most common, such as Vancouver or APA style, to others such as ISO 690, Harvard, MLA, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…Our analysis showed that each subject area adopts different styles within their periodical publications, as also observed by Tovaruela Carrión et al . (2017) and that there is a variation in the adoption of reference styles even among journals from the same discipline.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our analysis showed that each subject area adopts different styles within their periodical publications, as also observed by Tovaruela Carrión et al . (2017) and that there is a variation in the adoption of reference styles even among journals from the same discipline.…”
Section: Discussionsupporting
confidence: 86%
“…The wide variety of reference styles supports Tovaruela Carrión et al .’s (2017) arguments that the presentation of bibliographic references is one of the most frequent problems in scientific literature. In addition, the multiple coexisting editions of some reference styles, i.e.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation